Association of Left Atrial Epicardial Adipose Tissue with Electrogram Bipolar Voltage and Fractionation: Electrophysiologic Substrates for Atrial Fibrillation - Zghaib, Tarek (Heart Rhythm, 2016)
BACKGROUND: Epicardial adipose tissue (EAdT) is metabolically active and likely contributes to atrial fibrillation (AF) through the release of inflammatory cytokines into the myocardium or through its rich innervation with ganglionated plexi at the pulmonary vein ostia. The electrophysiological mechanisms underlying the association between EAdT and AF remain unclear. OBJECTIVE: Our study investigated the association of EAdT with adjacent myocardial substrate. METHODS: We studied 30 consecutive patients who underwent cardiac computed tomography as well as electro-anatomical mapping in sinus rhythm prior to an initial AF ablation procedure. Semiautomatic segmentation of atrial EAdT was performed and registered anatomically to the voltage map. RESULTS: In multivariable regression analysis clustered by patient, age (−0.01 per year) and EAdT (−0.29) were associated with log bipolar voltage as well as low-voltage zones (<0.5 mV). Age (OR=1.02 per year), male gender (OR=3.50), diabetes (OR=2.91), hypertension (OR=2.55), and EAdT (OR=8.56) were associated with fractionated electrograms and age (OR=2.80), male gender (OR=3.00), and EAdT (OR=7.03) were associated with widened signals. Age (OR=1.03 per year) and BMI (OR=1.06 per kg/m(2)) were associated with atrial fat. CONCLUSION: The presence of overlaying EAdT was associated with lower bipolar voltage and electrogram fractionation as electrophysiologic substrates for AF. EAdT was not a statistical mediator of the association between clinical variables and AF substrate. BMI was directly associated with the presence of EAdT in patients with AF.